DESAIN DAN PENGEMBANGAN CUSTOM DEVICE SEBAGAI SISTEM KONTROL GAME BEPAY - Zulkarnain, Andry Fajar; Mustamin, Nurul Fathanah; Maulida, Muti'a (INFO-TEKNIK, 2020)
BeatME is made by utilizing digital technology and network technology to make it easier for humans to channel their creativity in the field of music. With this convenience, it is expected that people who have always wanted to play music but are constrained by ability, knowledge, tools, cost, time, and location, can realize their desires and produce works. The BeatME game control system is a tool made by using Arduino as a game controller named. Based on the results of tests that have been done, it can be concluded that the device can send and receive data for communication with the Bepay game. And also equipped with a vibrating sensor and infrared to add the impression of drawing in its use. It is expected that with this test can be played by beginners and who are already accustomed to the game Bepay to become an interesting entertainment.